(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
“Sister Carrie” is one of the first novels that openly describes a number of problems of unemployment, moral decay, and social life in America. The article talks about the importance of society and personal inclinations in the decline of human moral values.